New Year-Themed Content Marketing Strategies to Build Emotional Engagement and Long-Term Relationships with Consumers - Rokhadi (ADMAN: Journal of Contemporary Administration and Management, 2024)
This study aims to explore how New Year-themed content marketing strategies can be used to build emotional engagement and long-term relationships with consumers. Through a literature review with a descriptive analysis approach, data was collected from 19 relevant articles obtained through Google Scholar between 1999 and 2024. The study found that New Year-themed content marketing can create strong emotional experiences, enhance consumer loyalty, and strengthen the relationship between brands and their audiences. Brands that connect with positive values and consumer aspirations, and offer relevant and personal experiences, are more likely to build long-term relationships. The implications of this research emphasize the importance of implementing marketing strategies that prioritize emotional engagement and relevance with consumers, especially through the use of social media and digital technologies. This research also identifies the importance of sustainability and social responsibility in seasonal-themed content marketing.